UPAYA PENINGKATAN KEMAMPUAN MEMBACA Al QUR’AN INDAH DENGAN METODE TILAWATI - Ummi Hani’ Farihah (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2021)
Reading the Qur'an must pay attention to the rules that have include: Tajwid Science, Gharib science, Makharijul Letters, and able to understand and pronounce long or short readings. So, in the process of learning to read the Qur'an, these rules must be studied and understood properly because if the rules are not properly understood, then the recitation of the Qur'an also becomes false. Effective teaching means teaching that students can understand perfectly. In the science of education it is often also said that proper teaching is teaching that functions in students.